-9(2-8)+4x+10=229

Simple and best practice solution for -9(2-8)+4x+10=229 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(2-8)+4x+10=229 equation:


Simplifying
-9(2 + -8) + 4x + 10 = 229

Combine like terms: 2 + -8 = -6
-9(-6) + 4x + 10 = 229

Multiply -9 * -6
54 + 4x + 10 = 229

Reorder the terms:
54 + 10 + 4x = 229

Combine like terms: 54 + 10 = 64
64 + 4x = 229

Solving
64 + 4x = 229

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-64' to each side of the equation.
64 + -64 + 4x = 229 + -64

Combine like terms: 64 + -64 = 0
0 + 4x = 229 + -64
4x = 229 + -64

Combine like terms: 229 + -64 = 165
4x = 165

Divide each side by '4'.
x = 41.25

Simplifying
x = 41.25

See similar equations:

| 8=3-5x | | 1+6x+5x=100 | | 7x(2+8)= | | -y=3x+6 | | -y^3x-2x^4y^3= | | 2y^2+4y-1=7y^2-7y+1 | | 378=(15+x)(12+x) | | d+99999999999999999990=999999999999999999 | | x+(x*4)=4 | | 12-2x=3x+22 | | 3.4c-1.2c=8.8 | | x-4/3+1=7/6 | | 5m+18=15-24-4m | | -k+2=-2k-2-4 | | 9(b+7)=9(b-5) | | 1(23)(-18)(2)= | | Y-39=-39 | | 8k-4k-8= | | (1)(23)(-18)(2)= | | 2-6j+8j=-2j-10 | | 8y-8-3y=12y-6 | | -5(r+9)=-53 | | 9(o+2)=3(o-2) | | 5.7+1.8n=0.84 | | 5d=9d-20 | | 15k^2-8=-2k | | 8-6x+x=2-3x | | 9-5z=12-6z+7 | | 83-x=93-2x | | .8(x+4)-.3x=1.7 | | n*2-12=34 | | 3y-6y^2=0 |

Equations solver categories